Results of the process and impact evaluation for selected government water supply and sanitation programs - Alma D. Porciuncula; Doreen C. Erfe; Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2016)
Past and present administrations have implemented water supply and sanitation (WSS) programs to increase the number of households with access to safe drinking water and sanitary toilet facilities. This study examines the President's Priority Program for Water and the Sagana at Ligtas na Tubig Para sa Lahat Program. It finds underachievement of targets, which was a result of institutional framework weaknesses, capacity and governance constraints, and fundamental gaps in program implementation. Given the remaining unmet needs in WSS, the study recommends that an improved successor program that also has a nationwide scope be designed. It also provides recommendations on how to improve the overall implementation of the successor program, the grant allocation and prioritization, the stakeholder participation, and funds management and disbursement. In addition, it presents a possible framework for a monitoring and evaluation plan of future WSS programs and a database that can be used in the future for ranking and prioritization, monitoring, and estimation of investment requirements.
Keywords: 330; water supply; sanitation; process evaluation; impact evaluation; WSS; Salintubig; P3W